MAIN TRENDS OF MEDIA CONSUMPTION IN RUSSIA IN THE CONDITIONS OF DYNAMICALLY CHANGING REALITY - A. Komarova (Вестник университета)
The article highlights the current problem of media consumption in Russia, the concept of media use as an active social practice is considered. The characteristics of the practice of media consumption in the modern world and their features are investigated. The comparative data of the dynamics of media consumption in Russia (by types of media television, Internet, radio and press desktop and mobile Internet are considered separately) are presented, the main trends of changes for the period from 2013 to 2017 are described.